2011
DOI: 10.1016/j.tetlet.2011.08.071
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Pictet–Spengler reactions of isatins for the synthesis of spiroindolones

Abstract: The condensation cyclization between isatins and 5-methoxy tryptamine catalyzed by chiral phosphoric acids provides spirooxindole tetrahydro-β-carboline products in excellent yields (up to 99%) and enantioselectivity (up to 98:2 er). A comparison of catalysts provides insight for the substrate scope and factors responsible for efficient catalytic activity and selectivity in the spirocyclization. Chiral phosphoric acids with different 3,3′-substitution on the binaphthyl system and opposite axial chirality affor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(46 citation statements)
references
References 35 publications
1
45
0
Order By: Relevance
“…Almost at the same time, Franz reported similar reactions using catalyst 147 or 148 (Scheme ) 100. Interestingly, they found that the same configuration of spiro oxindolone product was obtained for both the ( S )‐ 147 and ( R )‐ 148 , indicating that the substitution on the binaphthyl system directs the sense of enantioselection.…”
Section: Six‐membered Fused Ringsmentioning
confidence: 82%
“…Almost at the same time, Franz reported similar reactions using catalyst 147 or 148 (Scheme ) 100. Interestingly, they found that the same configuration of spiro oxindolone product was obtained for both the ( S )‐ 147 and ( R )‐ 148 , indicating that the substitution on the binaphthyl system directs the sense of enantioselection.…”
Section: Six‐membered Fused Ringsmentioning
confidence: 82%
“…136 Substituted isatins were used in Michael reaction for the synthesis of compounds 124, using chiral sterically congested phosphoric acids, such as compound 125, for improving the enantioselectivity of the reaction (Scheme 62 …”
Section: Phosphorus Compounds As Catalysts For Reactions Of Isatinsmentioning
confidence: 99%
“…Pyrrolidinyl spirooxindole constitutes an important class of spirooxindoles, especially in naturally occurring alkaloids such as cyanogramide (Figure ), spirotryprostatin A and B, pteropodine, elacomine, horsifoline and gelsemine which possess a wide range of biological activities like antimicrobial, anticancer, antifungal, etc . Inspired by the biological significance of these spirocyclic heterocyclic motifs,– versatile synthetic strategies have been directed towards the synthesis of this class of molecules employing 1,3‐dipolar cycloadditions,– Morita‐Baylis‐Hillman reaction, Pictet‐spengler reaction and so forth. Among them, the most successful method is 1,3‐dipolar cycloaddition reaction of azomethine ylide with various substituted dipolarophiles to construct spiro[pyrrolidin‐2,3′‐oxindoles] scaffold –…”
Section: Introductionmentioning
confidence: 99%